Consumer-oriented food system innovations to increase consumer awareness and fruit and vegetable intake in urban areas of Nigeria and Viet Nam - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Effects of the materials on consumer behavior has been evaluated over three rounds of piloting. Adjustments were made after each round. In 2021, piloting was completed and the prototypes of the materials have been made available for uptake. Results will be published after A4NH ends.